Laparoscopic left hemihepatectomy guided by real-time indocyanine green fluorescence imaging using the arantius-first approach - Jiaguo Wang; Jie Xu; Kai Lei; Ke You; Zuojin Liu (World Journal of Surgical Oncology, 2023)
Abstract Background and objective Laparoscopic hepatectomy approaches, including major hepatectomy, were rapidly developed in the past decade. However, standard laparoscopic left hemihepatectomy (LLH) is still only performed in high-volume medical centres. In our series, we describe our technical details and surgical outcomes of LLH. Methods Thirty-nine patients who underwent LLH in our institute were enrolled in the study. Among these, 13 patients underwent LLH guided by real-time ICG fluorescence imaging using the Arantius-first approach (ICG-LLH group), and the other 26 underwent conventional LLH (conventional LLH group). Demographic characteristics and perioperative data were retrospectively collected and analysed. We compared the technical and postoperative short-term outcomes of the two groups. Results There were no significant differences in the demographic or clinicopathological characteristics of the patients in the two groups. ICG-LLH required significantly fewer pringle manoeuvres (1 vs. 3 times, p < 0.0001), had a shorter parenchyma dissection time (26 vs. 78 min, p < 0.001), and required fewer vessel clips (18 vs. 28, p < 0.001). Although there was no significant difference, the ICG-LLH group had less bile leakage (0 vs. 5, p = 0.09) and less blood loss (120 vs. 165, p = 0.119). There were no significant differences in the overall complication or R0 resection rates between the two groups. Conclusion Our data demonstrate that laparoscopic left hemihepatectomy guided by real-time ICG fluorescence imaging using the Arantius-first approach is safe and feasible in selected patients, thus improving the fluency of the surgical procedure and postoperative short-term outcomes.